Investigation of the relationship between eating attitude and body composition of patients with anxiety disorders - Hülya Ertekin (SERNEV, 2019)
Introduction: The aim ofthis study was to evaluate the relationship between eating attitude, bodycomposition and disease severity in patients with anxiety disorders.Methods: This isa cross-sectional case-control study conducted between January-March 2018 inClinic of Psychiatry of Çanakkale Onsekiz Mart University Medical Faculty ofHospital. Beck depression scale (BDI), beck anxiety scale (BAI) and eatingattitude test (EAT) were applied to patients diagnosed as anxiety disorderaccording to DSM-5 criteria and to healthy controls. Body compositions of all participantswere measured by Bioimpedance Analysis (BIA). Results: Twenty-fivepatients with anxiety disorders and 25 healthy controls were included in thestudy. The BDI and BAI scores of the participants measured the severity ofanxiety and depressive symptoms were statistically higher than the controls. (p lt;0.001). There were statistically significant positive correlations betweenBDI and BAI, EAT and BMI (p = 0.029, r = 0.436; p = 0.001, r =.630,respectively). There was a statistically significant positive correlationbetween EAT and BMI (p = 0.027, r = 0.441). There were no statisticallysignificant differences between two groups in terms of body fat ratios.Conclusions: Our study shows that patients with anxiety disorders should be evaluatedfor obesity and related factors and necessary recommendations should be made.